Abundance and diversity of host-seeking adult female mosquitoes in a coastal ecosystem in southern Mexico. - Julio César Canales-Delgadillo; Nallely Vázquez-Pérez; Vicente Viveros-Santos; Rosela Pérez-Ceballos; José Gilberto Cardoso-Mohedano; Arturo Zaldívar-Jiménez; Omar Celis-Hernández; Alejandro Gómez-Ponce; Martín Merino-Ibarra (PLoS Neglected Tropical Diseases)
Mosquito diversity influences disease risk because only certain species transmit pathogens, making the identification of species assemblages essential. To better understand mosquito diversity in the southern Gulf of Mexico, we conducted a study on Isla del Carmen, Campeche, from September 2019 to December 2020. Adult mosquitoes were collected using buccal aspirators during 24-hour cycles in mangrove and low-semideciduous forest patches across three climate seasons: norte, rainy and dry. Sampling occurred every four hours, and species were identified. Hill numbers of order q = 0, q = 1, and q = 2, non-binomial GLMs, NMDS, PERMANOVA, and generalized estimating equations were used to analyze mosquito diversity, abundance, and phenology. We collected 21,424 mosquitoes from 11 genera, 26 species, and four morphospecies. The mosquito abundance and richness peaked during the norte season (β = 1.057, z = 2.480, p = 0.013), with the season being the primary determinant of abundance (PERMANOVA, F = 7.229, R² = 0.512, p = 0.003). The vegetation type and sampling hour showed effects only when excluding the eudominant Aedes taeniorhynchus. The top five genera, Aedes, Psorophora, Mansonia, Culex and Anopheles, exhibited distinct phenological patterns, with abundance peaking between September 2019 and February 2020. Isla del Carmen is a key region for mosquito diversity in the Yucatan Peninsula, hosting species known to transmit pathogens to humans and wildlife. Our findings highlight the norte season, when cooler temperatures and moderate rainfall are present, as a critical period for mosquito activity, emphasizing the need for targeted vector surveillance and control efforts during this time in the region. This study provides valuable insights into mosquito community dynamics and their implications for public health in coastal areas of southern Mexico.